Pengaruh Pemanfaatan Program Bantuan Sosial terhadap Tingkat Kemiskinan di Desa Pelita Hijau Kabupaten Bone Bolango - Putri Aulia Husain; Roy Hasiru; Fatmawaty Damiti; Melizubaida Mahmud; Ardiansyah Ardiansyah (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This research aims to analyze the influence of social assistance program utilization on the poverty level in Pelita Hijau Village, Bonepantai Sub-District, Bone Bolango Regency. This research utilizes a quantitative approach with a descriptive method. The sample consists of all 57 recipients of social assistance in the form of BLT (Bantuan Langsung Tunai or Direct Cash Assistance) and BPNT (Bantuan Pangan Non-tunai or Non-Cash Food Assistance) in Pelita Hijau Village. The data collection techniques used in this research include initial observations, questionnaires, and documentation. The data analysis technique applied is simple linear regression. The findings indicate a positive and significant influence of social assistance on the poverty level, with the determination coefficient value from the regression model obtained at 0.300. The findings also showthat the correlation coefficient (R) suggests a moderately strong influence. The determination coefficient (R Square) represents the percentage of the influence of variable X (social assistance) on variable Y (poverty level). In contrast, the remaining70% in influencedby other variables not examined in this research.